Retinoprotective effects of ascovertin under light influence in conditions of hyperglycemia - S. V. Logvinov; M. B. Plotnikov; Ye. Yu. Varakuta; A. A. Zhdankina; A. V. Potapov; Ye. P. Mikhulya (Бюллетень сибирской медицины, 2007)
Experiments performed on white outbred 100 rats showed that light impact with the intensity of 6 000 lx y during 6 hours and radiation in the setting of alloxanic diabetes caused injury of most structural components of retina and significant microcirculatory disturbances in the sclera. Starting with 7 days after radiation, retina damages had focal character which was more evident during radiation in the setting of alloxanic diabetes. However, prolonged injection of ascovertin led to decreased decstruction and improved hemodynamics which was expressed in reliable decreasing focal area by 2.1 times after light impact and by 1.4 times after radiation in the setting of alloxanic diabetes.